Moving and Dancing Towards Decolonisation in Education: An Example from an Indigenous Australian Performance Classroom - Mackinlay, Elizabeth (The Australian Journal of Indigenous Education, 2005)
Abstract In this paper I explore the special type of thinking, moving and dancing place which is opened up for decolonisaton when students engage in an embodied pedagogical practice in Indigenous education. I examine what decolonisation means in this context by describing the ways in which the curriculum, the students and me, and more generally the discipline of ethnomusicology itself, undergo a process to question, critique, and move aside the pedagogical script of colonialism in order to allow Indigenous ways of understanding music and dance to be presented, privileged and empowered. Key questions are: What is the relationship between embodiment and disembodiment and decolonisation and colonisation? In what ways is embodiment more than, or other than, the presence of moving bodies? In what ways is performativity an aspect of power/knowledge/subject formations? How can it be theorised? What could the pedagogical scripts of decolonisation look like?